Adhesion Factor (α) of Drilled Piles in Clay Shale with Static and Dynamic Load - Sudjatmiko, Eddy Triyanto; The Cin Hok (Indonesian Geotechnical Journal, 2026)
Adhesion factor (α) is one of the significant parameters in calculating the bearing capacity of pile foundations, both for driven piles and bored piles in clay soils. In practice, the α value is usually estimated based on the available empirical correlations. The applicability of this correlation for bored pile installed in expansive soil and clay shale is questionable. Clay shale is known as one of the problematic soils, due to its physical properties that rapidly soften once exposed to water/moisture and loss of pressure. This physical sensitivity becomes crucial in bored pile constructions. Especially in the drilling and casting process as the soil is exposed to water and loss of horizontal pressure causing reduction in soil shear strength. This study investigates the load transfer behavior of a bored pile installed in clay shale formation. The pile, instrumented with vibrating wire strain gauges, was axially loaded through dynamic and static load test up to 700 tons. The strain gauges provide accurate strain measurement of each pile segment, proportional to the stress induced. Through the pile load-settlement, t-z and q-z curves, the load transfer mechanism and interaction between bored pile and the clay shale soil can be analyzed. By performing back analysis, the actual skin friction (fs), and adhesion factor (α), of bored piles in clay shale can be determined. The results show that in clay shale that have experienced slaking (30 < NSPT < 70), the adhesion factor (α) = 0.12~0.18. While for fresh clay shale (NSPT > 70), the adhesion factor (α) = 0.32~0.35. These values are significantly lower than α = 0.55 which is usually applied in practice; as well as some previous studies, including the value recommended by Reese and Wright (1979).